Geographical offender profiling: Dragnet's applicability on a Brazilian sample. Issue 2 (20th February 2018) - Lino, Denis; Calado, Bruna; Belchior, Danielly; Cruz, Mayara; Lobato, Aline
Abstract: Even though geographical offender profiling is already widely used and researched in countries such as England, Canada, and United States, it is still severely overlooked in Brazil, as there are no researches on the subject using a Brazilian sample. Therefore, the present paper aims to start filling this gap by analysing the applicability of the geographical offender profiling and Dragnet on a sample of Brazilian serial killers. In order to achieve this objective, the authors collected data through police records on 15 serial killers that were active between June 2009 and June 2015, in the city of Campina Grande, Paraíba, Brazil. As a result, the circle hypothesis was confirmed, considering that 66.7% of the sample fell into the marauder category. Interestingly, the Dragnet's result accurately informed the area that contained the offender's base in the same cases in which the offender acted according to the marauder model. Also, other important correlations were found such as the influence of age, intelligence, resourcefulness, and method of approach on the distance travelled to commit a murder. Those results show that the geographical offender profiling can be effectively applied in Brazil and thus is a valid investigative tool to aid police officers in serial crimes investigations.